Transcriptome analysis reveals molecular targets of erythrocyte invasion phenotype diversity in natural Plasmodium falciparum isolates from Cameroon - Ngoh, Ines A.; Mane, Karim; Manneh, Jarra; Bojang, Fatoumata; Jawara, Aminata S.; Akenji, Theresia N.; Anong, Damian N.; D’Alessandro, Umberto; Amambua-Ngwa, Alfred (Frontiers in Parasitology, 2024)
Further understanding of the molecular mediators of alternative RBC invasion phenotypes in endemic malaria parasites will support malaria blood stage vaccine or drug development. This study investigated the prevalence of SA-dependent and SA-independent RBC invasion pathways in endemic P. falciparum parasites from Cameroon and compared the schizont stage transcriptomes in these two groups with the goal of uncovering the wider repertoire of transcriptional variation associated with the use of alternative RBC invasion pathway phenotypes. Two-colour flow cytometry-based invasion-inhibition assay against RBCs treated with neuraminidase, trypsin and chymotrypsin and deep RNA sequencing of schizont stages harvested in the first ex-vivo replication cycle in culture were employed in this investigation. RBC invasion phenotypes were determined for 63 isolates from asymptomatic children with uncomplicated malaria. Approximately 80% of the isolates invaded neuraminidase-treated but not chymotrypsin-treated RBCs, representing sialic acid (SA)-independent pathways of RBC invasion. The schizont transcriptome profiles of 16 isolates with invasion phenotypes revealed a total of 5136 gene transcripts, with 85% of isolates predicted at schizont stages. Two distinct transcriptome profile clusters belonging to SA-dependent and SA-independent parasites were obtained by data reduction with principal component analysis. Differential analysis of gene expression between the two clusters implicated in addition to the well characterized adhesins, the up-regulation of genes encoding proteins mediating merozoite organelle discharges as well as several conserved, virulent, merozoite associated and exported proteins. The latter majority have been shown to have structural and physiological relevance to RBC surface remodelling and immune evasion in malaria and thus, have potential as anti-invasion targets.